Epigenetic control of effectors in plant pathogens - Gijzen, Mark; Ishmael, Chelsea; Shrestha, Sirjana D. (Frontiers in Plant Science, 2014)
Plant pathogens display impressive versatility in adapting to host immune systems. Pathogen effector proteins facilitate disease but can become avirulence (Avr) factors when the host acquires discrete recognition capabilities that trigger immunity. The mechanisms that lead to changes to pathogen Avr factors that enable escape from host immunity are diverse, and include epigenetic switches that allow for reuse or recycling of effectors. This perspective outlines possibilities of how epigenetic control of Avr effector gene expression may have arisen and persisted in plant pathogens, and how it presents special problems for diagnosis and detection of specific pathogen strains or pathotypes.